Blackwater : the rise of the world's most powerful mercenary army - Scahill, Jeremy (Nation Books, 2007)
In this exposé by radical journalist Scahill, you will meet BLACKWATER USA, the world's most secretive and powerful mercenary firm. Based in the wilderness of North Carolina, it is the fastest-growing private army on the planet, with forces capable of carrying out regime change throughout the world. Blackwater protects the top US officials in Iraq, and yet we know almost nothing about the firm's quasi-military operations in Iraq, Afghanistan and inside the US. Blackwater was founded by an extreme right-wing fundamentalist Christian mega-millionaire ex-Navy Seal named Erik Prince, the scion of a wealthy conservative family that bankrolls far-right-wing causes. This book is the dark story of the rise of a powerful mercenary army, ranging from the blood-soaked streets of Fallujah to rooftop firefights in Najaf to the hurricane-ravaged US Gulf to Washington DC, where Blackwater executives are hailed as new heroes in the war on terror.--From publisher description.